2021
DOI: 10.1111/1365-2435.13788
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation to a structural biomaterial: Induced production of byssal threads decreases growth of a marine mussel

Abstract: The biomechanics of specialized mechanical structures produced by organisms provides crucial fitness advantages. The energetic cost associated with producing these structural materials and the resulting energetic trade‐off with growth, however, is rarely quantified. We integrate resource allocation to structural material production with an energetic framework by combining an experimental manipulation with an energetic model. Mytilid bivalves produce byssus, a network of collagen‐like threads that tethers indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 95 publications
(171 reference statements)
1
9
0
Order By: Relevance
“…Additionally, the decline in physiological condition of mussels within all laboratory treatments supports the conclusion that shell repair is energy-intensive. Given its importance to survival across a wide range of molluscan species, shell repair may impose energetic limitations on other physiological processes such as growth or reproduction [103]. Our results suggest that in areas where bivalves sustain a high rate of shell damage, it is possible that the costs associated with shell repair could compound over time, preventing smaller individuals from quickly surpassing the size range in which larger predators (e.g., sea stars, crustaceans) can handle them [104].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the decline in physiological condition of mussels within all laboratory treatments supports the conclusion that shell repair is energy-intensive. Given its importance to survival across a wide range of molluscan species, shell repair may impose energetic limitations on other physiological processes such as growth or reproduction [103]. Our results suggest that in areas where bivalves sustain a high rate of shell damage, it is possible that the costs associated with shell repair could compound over time, preventing smaller individuals from quickly surpassing the size range in which larger predators (e.g., sea stars, crustaceans) can handle them [104].…”
Section: Discussionmentioning
confidence: 99%
“…Biomineralization is an energy intensive process [85,86], and the added cost of shell repair (maintenance) could impose energetic limitations on other physiological processes such as growth or reproduction [87]. In areas where mussels sustain a high rate of shell damage, it is possible that the cost associated with shell repair could compound over time, preventing smaller individuals from quickly surpassing the size range in which larger predators (e.g., sea stars, crustaceans) can handle them [88].…”
Section: Discussionmentioning
confidence: 99%
“…The noise-induced decline in byssal thread production (i.e., the decrease in the diameter and volume of byssal thread, and the down-regulation of genes encoding structural proteins of byssal thread) might be due to limited energy availability. It has been shown that the energetic cost of byssal thread production is substantial, requiring 8-10% of a mussel's total energy expenditure (Hawkins and Bayne, 1985;Lurman et al, 2013;Roberts et al, 2021). However, studies have suggested that anthropogenic noise adversely affected the feeding behavior and metabolism activity of marine bivalves, including mussels, which seems to result in energy deficiency (Peng et al, 2016;Spiga et al, 2016;Shi et al, 2019;Wale et al, 2019;Vazzana et al, 2020).…”
Section: Discussionmentioning
confidence: 99%